SKRINING VIRTUAL DAN ELUSIDASI MODA IKATAN SENYAWA INHIBITOR ENZIM ELASTASE DAN HYALURONIDASE PADA BEBERAPA TANAMAN DENGAN AKTIVITAS ANTI-AGING - Mumpuni, Esti; Mulatsari, Esti; Noerfa, Tri Kumala (Jurnal Farmasi Indonesia, 2019)
Several studies on elastase enzymes and hyaluronidase enzymes that have the potential to be anti-aging have been previously published. Referring to the various results of the study, a virtual screening of 30 natural substances from 10 anti-aging plants and the binding mode elucidation of the active compound as an inhibitor of enzyme causing aging were carried out. This study aims to determine the inhibiting mechanism of antiaging compounds in plants and to model their interactions. Based on the results of the ChemPLP score from the docking simulation there were 4 active compounds was obtained which inhibited the elastase enzyme, namely : 2 compounds from orange plants (Citrus aurantium subsp. Amara), 1 compound from lavender flower (Lavandula angustifolia L.) and 1 compound from galangal striped plants (Alpinia zerumbet). While on the hyaluronidase enzyme obtained 11 compounds that actively inhibit the hyaluronidase enzyme there were 2 compounds from the galangal striped plant (Alpinia zerumbet), 3 compounds from the areca nut plant (Areca catechu L.) , 1 compound from the tea plant (Camellia sinensis Kuntze), 1 compound from the rose flower (Rosa centifolia L.) , 2 compounds from the orange plant (Citrus aurantium subsp. Amara), 1 compound from lavender (Lavandula angustifolia L.) and 1 compound from the seaweed (Eucheuma spinosum).